TERAPI "BER-BI" UNTUK MENINGKATKAN PERILAKU PROSOSIAL PADA SISWA TK DESA SEWULAN, MADIUN TAHUN 2014 - Muryanto, Hagus; Kadafi, Asroful; Trisnani, Rischa Pramana; Yuniar, Vivi (Jurnal Penelitian LPPM (Lembaga Penelitian dan Pengabdian kepada Masyarakat) IKIP PGRI MADIUN, 2015)
Nowadays, Children often have problems in order to adapt to their environment on a daily, one of the important problems to overcome is the Prososial problem. The purpose of this research explicitly to improve the Prososial behavior Kindergarden students of Sewulan Dagangan Madiun in 2013/2014 by theraphy "Ber-Bi". In Our research used True-Experimental One Group Pretest Posttest Design. In this research the data analysis was conducted with statistics by calculating the percentage, the method of collection of data through observation and interview. The results of this research have increase the Prososial behavior by 35% from pre-test results of 38% to 73% after treatment with the Bingo game. This research is expected to contribute information about how to increase of the Prososial behavior Kindergarten students by Bingo game.Â Keyword: Prososial, Games Bingo Card